2017
DOI: 10.3897/mbmg.1.13709
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling higher trophic level interactions in the cabbage aphid food web using high-throughput DNA sequencing

Abstract: The lack of understanding of complex food-web interactions has been a major gap in the history of biological control. In particular, a better understanding of the functioning of pest food-webs and how they vary between native and invaded geographical ranges is of prime interest for biological control research and associated integrated pest management. Technical limitations associated with the deciphering of complex food-webs can now be largely overcome by the use of high throughput DNA sequencing techniques su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The public availability of DNA barcodes will facilitate future forensic studies on host‐parasitoid associations and serves as the foundation upon which additional species can be added to improve the utility of this tool for analysis of trophic interactions between native and exotic species in this system. Future studies employing next‐generation DNA sequencing (NGS) or metabarcoding could make use of these sequence data to characterize all possible trophic interactions simultaneously, as has been shown in aphid‐parasitoid associations (Lefort, Wratten, Cusumano, Varennes, & Boyer, ) and in host‐parasitoid associations in forest dwelling Lepidoptera and Hymenoptera (Šigut et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public availability of DNA barcodes will facilitate future forensic studies on host‐parasitoid associations and serves as the foundation upon which additional species can be added to improve the utility of this tool for analysis of trophic interactions between native and exotic species in this system. Future studies employing next‐generation DNA sequencing (NGS) or metabarcoding could make use of these sequence data to characterize all possible trophic interactions simultaneously, as has been shown in aphid‐parasitoid associations (Lefort, Wratten, Cusumano, Varennes, & Boyer, ) and in host‐parasitoid associations in forest dwelling Lepidoptera and Hymenoptera (Šigut et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…euchisti, the interaction strength is the greatest between Tr. euschisti and C. hilaris (Figure DNA sequencing (NGS) or metabarcoding could make use of these sequence data to characterize all possible trophic interactions simultaneously, as has been shown in aphid-parasitoid associations (Lefort, Wratten, Cusumano, Varennes, & Boyer, 2017) and in host-parasitoid associations in forest dwelling Lepidoptera and Hymenoptera (Šigut et al, 2017).…”
Section: Species-level Host-parasitoid Associationsmentioning
confidence: 99%
“…focussed on mass barcoding of samples for species delimitation and construction of identification databases. To date, no studies have demonstrated the utility of these approaches for detecting species interactions, although see Lefort, Wratten, Cusumano, Varennes, and Boyer () and Šigut et al. () for examples of parasitism using more conventional sample tracking methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, Shokralla et al provided limited reproducibility for readers with their workflow and Cruaud et al focussed on mass barcoding of samples for species delimitation and construction of identification databases. To date, no studies have demonstrated the utility of these approaches for detecting species interactions, although seeLefort et al (2017) andŠigut et al (2017) for examples of parasitism using more conventional sample tracking methods…”
mentioning
confidence: 99%